Is the lower return to immigrants' foreign schooling a postarrival problem in Canada? - Yigit Aydede; Atul Dar (IZA Journal of Migration, 2017)
Using the 2006 Canadian Census, this paper investigates the lower return to immigrants' foreign education credentials after adjusting for their occupational matching in hosting labor markets. We develop two continuous indices that quantify the matching quality of the native-born in both horizontal (fields of study) and vertical (educational degrees) dimensions. This allows us to separate the effects of immigrants' occupational attainment and their foreign schooling quality on wage earnings by measuring immigrants' occupational match relative to that of native-born. Our findings indicate that the lack of portability in immigrants' foreign credentials may not be addressed effectively by postarrival policies as the results show that a significant and persistent poor matching quality for internationally educated immigrants cannot substantiate the lower return to their foreign education credentials.
Keywords: J6; J15; J61; 330; Return to education; Occupational mismatch; Immigration